Comparative Evaluation of Hydrogen Peroxide and Povidone-Iodine as Intra-operative Scolicidal Agents for Hydatid Cyst Management - Hamdy D. Elayouty; Ali M. Baterfy; Soliman H. Alkamash; Ahmed H.Dosoky (Medical Science: Recent Advances and Applications Vol. 5, 2025)
Background: Pulmonary echinococcosis is caused by the small tapeworm Taenia echinococcus, which commonly produces hydatid cystic disease of the liver. As hydatid cysts enlarge, they compress the surrounding parenchyma, damaging the surrounding tissues by mechanical and toxic factors. Secondary bacterial infections complicate the picture in 10 to 25% of cases, with either spontaneous or traumatic rupture in 5-10% of the cases. Objectives: A prospective randomised study designed to compare results of intra-operative applications of povidone-iodine with those of hydrogen peroxide during surgery for hydatid cysts. Methods: This study includes 160 patients with pulmonary and/or hepatic univesicular hydatid cysts who were admitted between 1st March 2004 through 29th February 2008, at the Unit of Chest Surgery, Hadhramout University Hospital, Almukalla, Yemen. Group A consisted of 80 patients for whom hydrogen peroxide was used; Group B consisted of 80 patients for whom Povidone-Iodine, was used. Each cyst was examined both macroscopically and microscopically to identify the effects of the used scolicidal agent on the wall. Postoperatively, patients received Albendazole as a scolicidal drug for one year. Follow-up times ranged between 48 and 84 months. Chest x-rays and abdominal ultrasound examinations were performed every six months to detect any recurrences. Sample and data percentages, mean, and the standard deviation were used to report data variations, using a bivariate analysis (SPSS Ltd, Quarry Bay, Hong Kong) Results: There was no perioperative mortality in either of the two groups. Group A: one case of postoperative prolonged airleak and two cases of wound infection. No recurrences were reported. Mean hospital stay was 5.5 ± 1.1 days. Group B: two cases of prolonged air leak, three cases of persistent cough and hemoptysis, one developing bronchopleural fistula that healed (air leak ceased after 19 days), two cases of wound infection, one had subphrenic abscess, nine cases of recurrences, one on the diaphragmatic pleura, two with deep chest wall cysts at sites of thoracostomy tubes, four intraperitonial recurrences, two in the same liver lobe. Recurrences occurred in 11% of the subjects (9/80; p value = 0.028). The mean hospital stay was 9.6 ± 1.5 days. On histologic examination of Group A, the cyst wall lost its integrity, lustre and viability and became friable. In Group B, the cyst wall maintained most of its lustre, integrity, and viability and did not become friable. Moreover, microscopic examination of sections in the wall of cysts postoperatively showed that in cysts injected with 10 % Povidone-Iodine, the inner layer of cyst wall contained not only germinal pyknotic cells, but also some cells with nuclear fragmentations (karyorrhexis). Conclusions: Hydrogen peroxide is a more effective and safer scolicidal drug than Povidone-Iodine, as shown by the differences in mean duration of hospital stay and postoperative recurrence rate significance. Statistical significance of recurrent cases among patients treated with povidone iodine indicates that it is inferior to hydrogen peroxide in this study. However, further research needs to be performed using higher doses of Albendazole for much longer periods, up to several years. The study recommends that Albendazole be administered in high doses in all cases of recurrence that develop during the first year. The impact of this infectious disease in endemic areas is such that continuous, focused research is warranted.